Decision Support System in Determining the Location of Village Health Services (Puskesmas) in Pagar Merbau District Using the Profile Matching Method - Wan Wimar Yahya; Fristi Riandari (Journal of Intelligent Decision Support System (IDSS), 2021)
Community health center (puskesmas), is a health service facility that organizes public health efforts and first-level individual health efforts, and prioritizes promotive and preventive efforts. In accordance with geographical conditions, area size, transportation facilities, and population density in the working area of the puskesmas so that the puskesmas services are accessible to the population, to assist the smooth process of services that will make it easier for the community. Therefore, to assist in determining an ideal puskesmas development location, a Decision Support System (DSS) is used, the process of calculating the results of determining the location of the puskesmas construction using the Profile Matching method. As for the alternatives of this study, 6 villages were taken, namely Tanjung Mulia, Sumberejo, Sidodadi, Pagar Merbau II, Sidoarjo Satu Pasar Miring, and Bandar Dolok. And from the results of calculations using the Profile Matching method, it displays the ranking of the results of determining the location, where the highest value is in Tanjung Mulia village with a value of 3.69 so that it can be used as a solution or consideration in determining the location of the puskesmas to be built.